Technical Limits in Prescriptive Building Cultures and Tectonic Approaches: Challenges of Turkish Cypriot Architects - Yazdani, Kamiar; Hurol, Yonca (Mdpi, 2025)
Prescriptive building culture, as a form of determinism, shapes architects' tectonic approaches by imposing prescriptive technical limits (PTLs) during the building process. Exploring PTLs provides a foundation for describing overarching tectonic approaches in practice that have not been systematically studied. This research provides a comprehensive overview of emerging PTLs among Turkish Cypriot architects in Northern Cyprus, examining their types, sources, emergence stages, root causes, and impact on tectonic design strategies. The study employed mixed-methods Sequential Explanatory Design (SED), combining survey and interview data. Findings reveal that architects mainly adopt conservative tectonic approaches in response to PTLs, reflecting limited innovative attitudes in technical and structural design, with rare tendencies towards more innovative strategies. Qualitative analysis maps structural engineers and legal frameworks as primary initiators, while PTLs mainly occur during preliminary design, construction documentation, and application visa stages. The key contributions are: (i) a transferable coding framework linking PTLs' initiators, stages, and effects; (ii) empirical evidence of predominant affirmative tectonic approaches in a prescriptive, seismic context; (iii) identified innovative design attitudes; and (iv) a regionally grounded dataset informing comparative studies. The uncovered indicative patterns also provide an applicable model for examining PTLs and tectonic approaches worldwide across other prescriptive cultures and seismic regions.
Keywords: prescriptive technical limits; reinforced-concrete frame structures; seismic zones; Northern Cyprus; innovative design attitudes; sequential explanatory design research